An integrated approach to identify normal tissue expression of targets for antibody‐drug conjugates: case study of TENB2. (20th December 2012) - Boswell, C Andrew; Mundo, Eduardo E; Firestein, Ron; Zhang, Crystal; Mao, Weiguang; Gill, Herman; Young, Cynthia; Ljumanovic, Nina; Stainton, Shannon; Ulufatu, Sheila; Fourie, Aimee; Kozak, Katherine R; et al.
Abstract : Background and Purpose: The success of antibody‐drug conjugates (ADCs) depends on the therapeutic window rendered by the differential expression between normal and pathological tissues. The ability to identify and visualize target expression in normal tissues could reveal causes for target‐mediated clearance observed in pharmacokinetic characterization. TENB2 is a prostate cancer target associated with the progression of poorly differentiated and androgen‐independent tumour types, and ADCs specific for TENB2 are candidate therapeutics. The objective of this study was to locate antigen expression of TENB2 in normal tissues, thereby elucidating the underlying causes of target‐mediated clearance. Experimental Approach: A series of pharmacokinetics, tissue distribution and mass balance studies were conducted in mice using a radiolabelled anti‐TENB2 ADC. These data were complemented by non‐invasive single photon emission computed tomography – X‐ray computed tomography imaging and immunohistochemistry. Key Results: The intestines were identified as a saturable and specific antigen sink that contributes, at least in part, to the rapid target‐mediated clearance of the anti‐TENB2 antibody and its drug conjugate in rodents. As a proof of concept, we also demonstrated the selective disposition of the ADC in a tumoural environment in vivo using the LuCaP 77 transplant mouse model. High tumour uptake was observed despite the presence of the antigen sink, and antigen specificity was confirmed by antigen blockade. Conclusions and Implications: Our findings provide the anatomical location and biological interpretation of target‐mediated clearance of anti‐TENB2 antibodies and corresponding drug conjugates. Further investigations may be beneficial in addressing the relative contributions to ADC disposition from antigen expression in both normal and pathological tissues.